2017
DOI: 10.1093/cid/cix704
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Viremia and Specific Organ Damage in Ebola Patients: A Cohort Study

Abstract: This study provides evidence to support that Ebola virus may have a direct role in muscular damage and imbalance of the coagulation system. We did not find strong evidence suggestive of a direct role of Ebola virus in kidney damage. The role of the virus in liver damage remains unclear, but our evidence suggests that acute severe liver injury is not a typical feature of Ebola virus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…Similar elevations were seen in our data. A study of APTT values in Sierra Leonean patients reported elevation in all cases (mean = 68.4 s), but greater elevation in fatal cases (mean = 84.9 s) compared to survivors (mean = 49.6 s) [25] leading to the hypothesis that coagulation parameters “may have value as a potential prognostic indicator of disease severity” in patients with EVD [23]. Our data indicated a similar prognostic possibility.…”
Section: Discussionsupporting
confidence: 66%
“…Similar elevations were seen in our data. A study of APTT values in Sierra Leonean patients reported elevation in all cases (mean = 68.4 s), but greater elevation in fatal cases (mean = 84.9 s) compared to survivors (mean = 49.6 s) [25] leading to the hypothesis that coagulation parameters “may have value as a potential prognostic indicator of disease severity” in patients with EVD [23]. Our data indicated a similar prognostic possibility.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, our choice to consider past exposure to Ebola virus as an explanatory variable for current malaria parasite infection in our analysis was arbitrary, and additional analyses confirmed that reversing the positions of the 2 pathogens in the model did not qualitatively change the observed association pattern (Appendix Table 6, Figures 5, 6). Furthermore, a biological mechanism of interaction between the 2 pathogens with the potential to cause the association found here (such as persistent inflammatory processes in EVD survivors [10,27,28] or damage to specific tissues targeted by both pathogens [29,30]) remains to be elucidated. We do, however, point out that the mechanism is not likely to be general or the result of immunosuppression (e.g., because of AIDS) because neither of the 2 common filarial infections included as co-factors (L. loa and M. perstans) were risk factors for infection with Plasmodium parasites (Figure 3) and Ebola virus exposure (Appendix Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Different factors, like delay in admission, organ failure, comorbidities, complications, factors not changed by the availability of intensive care, contribute to the mortality in patients with “low” Ebola viral load (LVL < 7.5). Patients with very high viral load (LVL > 8.5) may have a very limited benefit from intensive care support without effective antiviral treatment, because of the rapid progression of EVD to fatal multiple organ failure [ 28 ]. Only exceptionally it was possible to buy enough time for the immune system to clear the virus and reverse organ failure.…”
Section: Discussionmentioning
confidence: 99%